Electrochemical behaviour and surface analysis of chalcopyrite in alkaline glycine solutions - O'Connor, G.; Lepkova, Katerina; Eksteen, Jacques; Oraby, Elsayed (Elsevier, 2018)
© 2018 Elsevier B.V. Electrochemical experiments with a chalcopyrite rotating disk electrode were carried out in alkaline glycine solutions. This showed no apparent passivation behaviour during anodic dissolution that is observed in acid solutions. The current increased with applied potential from the open circuit potential with no resemblance to the passivation region seen in acid solutions. A loosely held porous layer developed on the surface consisting largely of iron oxyhydroxides that had a limited effect on the anodic current. Elemental sulfur and a disulfide species were detected using XPS and Raman spectroscopy but did not passivate the surface as has been proposed for acid solutions. The disulfide species is sometimes used to infer a metal deficient sulfide or polysulfide that is responsible for passivation but in this study it had no passivating influence. Current-potential curves showed features of a non-ideal semiconductor that were explained by charge transfer via surface states.